2015
DOI: 10.1371/journal.pone.0116402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Glycosylation Site Removal in Archaellins on the Assembly and Function of Archaella in Methanococcus maripaludis

Abstract: In Methanococcus maripaludis S2, the swimming organelle, the archaellum, is composed of three archaellins, FlaB1S2, FlaB2S2 and FlaB3S2. All three are modified with an N-linked tetrasaccharide at multiple sites. Disruption of the N-linked glycosylation pathway is known to cause defects in archaella assembly or function. Here, we explored the potential requirement of N-glycosylation of archaellins on archaellation by investigating the effects of eliminating the 4 N-glycosylation sites in the wildtype FlaB2S2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Transmission electron microscopy of Methanococcus maripaludis cells was performed as described previously (Ding et al, 2015). Briefly, cells were collected from an overnight culture by centrifugation, resuspended in 2 % (w/v) NaCl and placed on 200-mesh carbon-coated copper grids.…”
Section: Tryptic Digestion and Liquid Chromatography (Lc)-msmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy of Methanococcus maripaludis cells was performed as described previously (Ding et al, 2015). Briefly, cells were collected from an overnight culture by centrifugation, resuspended in 2 % (w/v) NaCl and placed on 200-mesh carbon-coated copper grids.…”
Section: Tryptic Digestion and Liquid Chromatography (Lc)-msmentioning
confidence: 99%
“…Methanococcus maripaludis is considered a model archaeal organism (Leigh et al, 2011) and one of the best-studied archaea with regard to its archaella (Chaban et al, 2007;Ding et al, 2015;Jarrell et al, 2011;VanDyke et al, 2009). This study reports on a variety of growth conditions and the effect they have on archaellation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though N-linked glycosylation is widespread in Archaea, the study of N-linked glycosylation pathways by both genetic and structural methodologies is concentrated on a few model species (4), including the thermoacidophile Sulfolobus acidocaldarius (5-9), the halophile Haloferax volcanii (10)(11)(12)(13)(14), and the methanogens Methanococcus voltae (15,16) and Methanococcus maripaludis (17)(18)(19)(20)(21)(22)(23). In general, the archaeal N-linked glycosylation pathway contains aspects of both the eukaryotic and bacterial systems, with additional domain-specific traits that include unique glycan structures, a variety of linking sugars, and unusual dolichol carri- Citation Siu S, Robotham A, Logan SM, Kelly JF, Uchida K, Aizawa S-I, Jarrell KF.…”
mentioning
confidence: 99%
“…In S. acidocaldarius, mutants producing a truncated N-glycan were shown to have severely reduced motility (7), although recent studies indicate that strains engineered to lack all six glycosylation sites in the archaellin FlaB were still motile (9). Recent studies have also shown that for FlaB2 of M. maripaludis, at least one of the four sequons used for N-glycan attachment must be occupied for archaellum assembly to occur (22), and for H. volcanii all sequons are necessary (14).…”
mentioning
confidence: 99%